KAJIAN KEMAMPUAN POHON PADA LANSKAP ALUN – ALUN PANCASILA DALAM MENYERAP KARBON DAN PARTIKEL TIMBAL - Adiantoro, Haris; Sutrisno, Alfred Jansen (Fakultas Pertanian, Universitas Janabadra, 2024)
activities. Such as, exercising, playing and relaxing. However, there is a problem that arises, namely a decrease in air quality due to emissions or exhaust gas from vehicles around the square. This is because the square is surrounded by the main road of Salatiga City. The aim of this research is to assess the ability of trees around the Alun-alun to absorb carbon and lead particles. The research method used was an exploration method where a total of 112 trees were analyzed for their ability to absorb carbon. Then trees that fall within a 5 meter radius around the road are samples for analysis of their ability to absorb lead, where the total number of trees sampled is 8 trees. Carbon absorption was assessed using the allometric equation while lead absorption used AAS (Atomatic Absorption Spectrophotometry). The average result of tree carbon uptake was 7,887 tonnes/ha, where the highest uptake was the Banyan tree at 70,267 tonnes/ha, the Angsana tree 20,046 tonnes/ha and the lowest was the Glodogan Tiang tree at 0.017 tonnes/ha. The lead uptake results showed that the Glodogan Tiang tree had the highest uptake of 590,500 ppm/g and the lowest was the Japanese Cedar tree at 65,100 ppm/g. The conclusion of this research shows that carbon uptake is influenced by trunk diameter and tree height, while lead uptake is influenced by tree location and leaf characteristics.